1991
DOI: 10.1007/bf02424572
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between a nuclear and a mitochondrial mRNA of cytochrome c oxidase subunits, enzymatic activity and total mRNA content, in rat tissues

Abstract: Cytochrome c oxidase (COX), like other multi-subunit components of the respiratory chain, is controlled by both the nuclear and the mitochondrial genome. In order to find wether there is a close relationship between mRNAs encoded by the nucleus and by the mitochondrion, and between these mRNAs and enzyme activity, we compared six rat tissues (ventricle, liver, m. soleus, m. plantaris, and the white and red portions of m. gastrocnemius). We found a tenfold range for COX activity, a tenfold range for the content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Thus COX represents an excellent model for the study of holoenzyme assembly and mitochondrial biogenesis in response to physiological stimuli. Previous studies have indicated that the expression of nuclear and mitochondrial COX subunits is coordinated among tissues possessing a wide range of COX enzyme activities (12,17). However, the current evidence suggests that this may not be the case in response to T 3 at the mRNA level (40,44).…”
Section: Discussionmentioning
confidence: 65%
“…Thus COX represents an excellent model for the study of holoenzyme assembly and mitochondrial biogenesis in response to physiological stimuli. Previous studies have indicated that the expression of nuclear and mitochondrial COX subunits is coordinated among tissues possessing a wide range of COX enzyme activities (12,17). However, the current evidence suggests that this may not be the case in response to T 3 at the mRNA level (40,44).…”
Section: Discussionmentioning
confidence: 65%
“…Support for a transcriptional coordination between nuclear and mitochondrial genes has been provided by numerous reports (Hood et al 1989;Gagnon et al 1991;Van den Bogert et al 1993;Connor et al 1996;Heddi et al 1999). However, data from analysis of changes in mitochondrial transcription in response to thyroid hormones (Enriquez et al 1999) as well as data from reporter gene activity (Sewards et al 1994) have indicated that mitochondrial and nuclear transcription systems operate independently.…”
Section: Discussionmentioning
confidence: 93%
“…The parallel increase of nuclear and mitochondrial message may be simply due to similar effects of temperature on both nuclear and mitochondrial mRNA turnover, or it may involve a regulatory coordination of the two genomes via signal transduction pathways. A coordinate expression of nuclear and mitochondrially encoded subunits of CCO has been shown in different tissues of rat (14,20). Furthermore, an equimolar upregulation of mitochondrial and nuclear CCO gene products occurs during biogenesis of mitochondria induced by chronic stimulation of rat skeletal muscle or cold exposure of brown adipose tissue (21,24).…”
Section: R512 Temperature-dependent Cco Expressionmentioning
confidence: 99%